Human ABCB1 confers cells resistance to cytotoxic guanidine alkaloids from Pterogyne nitens - Satake, Kazuhiro; Tsukamoto, Megumi; Mitani, Yuji; Regasini, Luis Octavio [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Efferth, Thomas; Nakagawa, Hiroshi (Ios Press, 2015)
Multidrug resistance (MDR) caused by human ABCB1 (P-glycoprotein/MDR1) is one of the major obstacles in chemotherapy. To understand the mechanism of MDR by ABCB1 and circumvent the MDR, in the present study, we established human ABCB1-expressing cells (Flp-In-293/ABCB1 cells) and examined the cytotoxic effects of four guanidine alkaloids from Pterogyne nitens (galegine, nitensidine A, pterogynidine and pterogynine) using Flp-In-293/Mock and Flp-In-293/ABCB1 cells. The activity of ABCB1 in Flp-In-293/ABCB1 cells were confirmed by typical substrates for ABCB1 (taxol and vinblastine) in MTT assay. Flp-In-293/ABCB1 cells were also resistant to the four guanidine alkaloids as well as taxol and vinblastine compared to Flp-In-293/Mock cells although the four guanidine alkaloids exhibited cytotoxicity against the two Flp-In-293 cells. Furthermore, the four guanidine alkaloids were also found to stimulate the ATPase activity of ABCB1 in ATPase assays. These results suggest that ABCB1 can confer the resistance to the cytotoxic guanidine alkaloids by transporting them.
Keywords: ABCB1; P-glycoprotein; ATP-binding cassette (ABC) transporter; Guanidine alkaloids